Diorama as an Interactive Tool for Learning House Vocabulary: Diorama sebagai Media Interaktif untuk Pembelajaran Kosakata Rumah - Nayoan, Adinda Roro; Mandarani, Vidya; Megawati, Fika; Agustina, Sheila (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Effective learning media are crucial for enhancing language acquisition among elementary school students. Specific Background: Traditional teaching methods may not adequately engage students, highlighting the need for innovative approaches that foster interactive learning environments. Knowledge Gap: There is a lack of research on the application of three-dimensional teaching tools, such as dioramas, in vocabulary acquisition for English language learners. Aims: This study aims to develop a diorama as an interactive medium to teach house-related vocabulary in English to elementary school students. Results: The diorama features a visually appealing three-dimensional design and incorporates vocabulary targets identified by numbered sections. It employs velcro or fabric adhesive to facilitate the removal and placement of vocabulary terms, allowing students to match words with corresponding parts of the diorama. Novelty: This approach combines tactile and visual learning strategies, enhancing students' engagement and motivation in learning English vocabulary. Implications: The implementation of the diorama as a learning tool can significantly improve students' understanding of vocabulary, making it easier for them to connect words with their meanings through interactive activities in reading and speaking exercises. This innovative resource offers educators a novel method to enhance language learning in a classroom setting. Highlights: Interactive Learning: The diorama fosters engagement by allowing hands-on interaction with vocabulary. Visual Aid: Its three-dimensional design helps students better understand and remember target vocabulary. Motivation Boost: The innovative format encourages students to participate actively in English learning. Keywords: diorama, vocabulary, interactive learning, English education, elementary students